RNA-guided multiplex genome engineering using cas9 nucleases for crop improvement: A review - ANURAGI, HIRDAYESH; SRIJAN, AMBATI; JAIN, BHARAT TAINDU (The Indian Journal of Agricultural Sciences, 2018)
Crop improvement through genome editing techniques has aroused substantial excitement among agricultural scientists as it offers opportunities for precise and predictable modification directly in elite cultivars or accessions which are not possible by time-consuming conventional breeding schemes. CRISPR-Cas9, a recently evolved gRNA-guided nuclease technology, is crucial in plant genome modifications which enable us in carrying out rapid and extremely precise mutations at pre-determined genomic sites by using guide RNA which is complementary to the target locus.This targeted DNA is then cleaved by Cas9 nuclease to generate double-strand breaks (DSBs), followed by subsequent DNA repair via non-homologous end joining (NHEJ) or homology-directed repair (HDR) mechanisms leading to the disruption of gene functions in plants. Multiplexed CRISPR-Cas9 exploits multiple gRNA sequences for simultaneous editing of multiple sites within the same genome, demonstrating its efficiency over traditional gene pyramiding. CRISPR/Cas9 is relatively convenient and easier to implement technology that has proven to be extremely efficient and versatile as compared to previously developed tools like ZFNs and TALENs and hence, it has been considered as a revolutionary technique in crop genome editing. The technique is continuously evolving to produce variants with its application in enhancing the agricultural performance of most crops. Moreover, plants developed by this technique have been considered superior to transgenic plants due to non-involvement of foreign DNA, hence, alleviating safety issues associated with GM plants. The current review briefly emphasizes on the potentiality of this game-changing technology in revolutionizing the basic plant genetic research and plant breeding.